On the formation of lipid droplets in human adipocytes: the organization of the perilipin-vimentin cortex - Heid, Hans; Franke, Werner (PLOS ONE, 2014)
We report on the heterogeneity and diversity of lipid droplets (LDs) in early stages of adipogenesis by elucidating the cell and molecular biology of amphiphilic and cytoskeletal proteins regulating and stabilizing the generation of LDs in human adipose cells. A plethora of distinct and differently sized LDs was detected by a brief application of adipocyte differentiation medium and additional short treatment with oleic acid. Using these cells and highly specific antibodies for LD-binding proteins of the perilipin (PLIN) family, we could distinguish between endogenously derived LDs (endogenous LDs) positive for perilipin from exogenously induced LDs (exogenous LDs) positive for adipophilin, TIP47 and S3-12. Having optimized these stimulation conditions, we used early adipogenic differentiation stages to investigate small-sized LDs and concentrated on LD-protein associations with the intermediate-sized filament (IF) vimentin. This IF protein was described earlier to surround lipid globules, showing spherical, cage-like structures. Consequently - by biochemical methods, by immunofluorescence microscopy and by electron- and immunoelectron microscopy - various stages of emerging lipid globules were revealed with perilipin as linking protein between LDs and vimentin. For this LD-PLIN-Vimentin connection, a model is now proposed, suggesting an interaction of proteins via opposed charged amino acid domains respectively. In addition, multiple sheaths of smooth endoplasmic reticulum cisternae surrounding concentrically nascent LDs are shown. Based on our comprehensive localization studies we present and discuss a novel pathway for the LD formation.
Gesehen am 17.08.2018